The HBV seroprevalence and immune responses to hepatitis B vaccination among college students from four universities in China - Song, Yarong; Feng, Yongliang; Jiang, Feng; Xu, Xingyan; Yang, Peijuan; Liu, Minmin; Li, Lili; Du, Chaobi; Li, Huangyuan; Li, Qiong; Qiao, Jinge; Shi, Jing; et al. (Vaccine, 2025)
People without effective immunization are vulnerable to infection with hepatitis B virus (HBV). At present, there is no appropriate hepatitis B vaccination strategy for HBV-susceptible adults. We aim to assess the long-term effect of neonatal hepatitis B immunization and HBV markers among college students, so as to explore hepatitis B vaccination strategies suitable for high-risk group. The enrolled freshmen from four universities were initially tested for hepatitis B screening using colloidal gold test strips. Subjects with positive hepatitis B surface antigen (HBsAg) or negative hepatitis B surface antibody (anti-HBs) were further confirmed using Abbott reagents. HBsAg and anti-HBs double negative individuals were administered hepatitis B vaccination. Using Abbott reagents, we confirmed that among 3242 enrolled freshmen, 1604 (49.5 %) were negative for both HBsAg and anti-HBs, and 27 (0.8 %) were HBsAg-positive. Among the double negative freshmen, 1263 received hepatitis B vaccination. After the first and second dose of hepatitis B vaccine, the protective anti-HBs seroconversion rates reached 91.4 % and 98.5 %, respectively. Only one (0.1 %) freshman was still negative for anti-HBs after the third dose of hepatitis B vaccine. In addition, 96.3 % (104/108) of the fresmen who failed to achieve protective anti-HBs seroconversion after the first dose of hepatitis B vaccine had a baseline anti-HBs level < 2 mIU/mL. The HBsAg prevalence among college students has been significantly reduced after the integration of hepatitis B vaccine into Expanded Program on Immunization, but the rate of seroprotective anti-HBs among these students remains low. Hepatitis B vaccination or booster dose is advised for a high-risk group who have negative anti-HBs, and two doses of hepatitis B vaccine are advised for those with anti-HBs < 2 mIU/mL.